Evaluation of Aloe Vera (Aloe Barbadensis) Instant Powder on Bone and Tooth Development in Pregnant Women - Ida Rahmawati; Hapisah; Neny Setiawaty Ningsih; Emilda Sari; Waljuni Astu Rahman; Noor Adha Aprilea (Jurnal Penelitian Pendidikan IPA, 2024)
This study aimed to evaluate the physical, chemical, biological, stability, and clinical effects of aloe vera (Aloe barbadensis) instant powder on pregnant women. The research involved formulating the powder, assessing its physical properties (flow time, dwell angle, compressibility index), and conducting chemical analysis (phytochemical screening). Microbial contamination was tested using the Most Probable Number and Total Plate Count methods, and stability was assessed over two months. Clinical trials were conducted with two groups: one receiving the aloe vera instant powder and the other receiving calcium supplements (positive control), each consisting of 5 pregnant women for 10 days. The results showed that the powder had a flow time of 8.63 seconds, a dwell angle of 34.33°, and a compressibility index of 7.70%. Chemical screening revealed the presence of flavonoids, phenolics, tannins, saponins, steroids, and interquinones. No microbial contamination was detected, and the powder remained stable. Clinical trials showed a significant increase in red and white blood cells, hemoglobin, potassium, calcium, phosphorus, and magnesium levels in the group receiving the aloe vera instant powder. In conclusion, aloe vera instant powder is stable and enhances hematological parameters and mineral levels in pregnant women.